Negative Theology: Its Use and Christological Function in Late Antiquity and Subsequent Developments - Aakjær Steenbuch, Johannes (Verbum Vitae, 2023)
This article discusses the historical development of negative theology from its formulations in early Christianity to its later forms in Medieval Neo-Platonism. First analyzing how in early Christian thought negative theology was often used for a Christological purpose, the article goes on to discuss the implications of the Neo-Platonic notion of God as beyond being. While primarily applying a historical methodology, the article concludes by encouraging a rediscovery of the Christological orientation for negative theology found in its early Christian formulations.